The long-term impacts of vocational rehabilitation - Lars Westlie (University of Oslo, Department of Economics, 2008)
This paper investigates empirically how five different vocational rehabilitation (VR) programs affect the transition rate into employment, the consecutive monthly earnings and the employment duration. VR programs increase the employment probability of the participants, but this effect varies substantially between the different programs. VR programs also lead to more stable jobs while the impact on monthly earnings is of minor magnitude. The costs and revenues of the VR programs are calculated, based on the estimated model. The results of wage subsidies, public education and work training in ordinary firms are noteworthy. The employment effect is clearly the strongest factor relative to the job quality effects, in describing the economic return of the VR programs.
Keywords: C14; C15; C41; D61; I21; J24; J64; 330; Vocational rehabilitation; program evaluation; multivariate hazards; costbenefit analysis; Berufliche Rehabilitation; Berufliche Integration; Bewertung; Kosten-Nutzen-Analyse; Norwegen